Beneficial effects of psyllium on the prevention and treatment of cardiometabolic diseases. Issue 14 (4th July 2022) - Chen, Chen; Shang, Chang; Xin, Laiyun; Xiang, Mi; Wang, Yuling; Shen, Zihuan; Jiao, Linke; Ding, Fan; Cui, Xiangning
Abstract : Psyllium, especially its husk, has been widely used in food products. This review summarized the potential mechanisms of it in the prevention and treatment of cardiometabolic diseases and its applications in food systems. Abstract : Cardiometabolic diseases are reaching epidemic proportions worldwide. Dietary fiber intake can improve the risk factors associated with CMD. Psyllium, especially its husk, is one of the most widely used dietary fiber supplements, which is often used to enrich cereals and other food products. Numerous pharmacological studies have investigated the active ingredients and therapeutic effects of psyllium and its extracts, including antioxidant, anti-tumor, antidiabetic, hypotensive, anti-inflammation, neuroprotection, antidiarrheal, and antiviral activities. In this review, we will summarize the available studies on the therapeutic potential and possible mechanisms of psyllium in treating CMDs, such as hyperlipidemia, diabetes mellitus, and its complications, hypertension, hyperuricemia and obesity, and its applications in food systems.